Adaptive Organizational Intelligence Capability: A Dynamic Capability Perspective on Employee Adaptability - Miranda Tsintskiladze (Involvement International Journal of Business, 2026)
This study aims to conceptualize Adaptive Organizational Intelligence Capability (AOIC) as a higher-order dynamic capability that enables organizations to continuously interpret environmental changes, integrate strategic knowledge, and facilitate adaptive employee behavior. A qualitative multiple-case study was conducted across organizations undergoing digital transformation in the technology, financial services, manufacturing, and professional service sectors. Data were collected through semi-structured interviews with senior managers, human resource directors, team leaders, and employees, complemented by organizational documents, internal training materials, and workplace observations. The findings reveal that Adaptive Organizational Intelligence Capability consists of four interrelated dimensions namely environmental intelligence sensing, which continuously identifies technological and market changes; collective knowledge integration, which transforms distributed organizational knowledge into strategic insights; adaptive decision-making capability, which enables rapid and evidence-based organizational responses; and continuous learning orchestration, which promotes ongoing employee learning, experimentation, and behavioral adjustment. These dimensions collectively strengthen employees' cognitive flexibility, proactive problem-solving, resilience, and readiness to embrace organizational change. The study extends Dynamic Capability Theory by introducing Adaptive Organizational Intelligence Capability as a novel organizational capability that bridges strategic intelligence and employee adaptability within digitally transforming organizations. The proposed framework provides theoretical contributions to strategic management and organizational behavior literature while offering practical guidance for leaders seeking to cultivate adaptive workforces capable of sustaining organizational competitiveness in increasingly dynamic business environments.